1998
DOI: 10.1002/masy.19981270116
|View full text |Cite
|
Sign up to set email alerts
|

Adhesive liquid‐crystalline polymers

Abstract: The synthesis and characterization of liquid-crystalline polymers with possible good adhesive properties is reported. These polymers are prepared by alternating copolymerization of maleic anhydride and mesogenic alkenes. The spacer length m is varied (m = 2,3,4,6, 8 and 9) and methoxybiphenyl is used as the mesogenic group. The glass transition temperature decreases and the isotropization temperature increases with spacer length. Depending on the spacer length and temperature, Sg and SA,, mesophases can be obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

1998
1998
2001
2001

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…The mesomorphic behavior of poly(MA-co-methacrylate)s is different from that of polymethacrylates 8,13) and poly(MA-alt-1-alkene)s 16,17) . Although all polymers show a decrease of T g with spacer length, only the poly(MAalt-1-alkene)s show an increase in T i with spacer length.…”
Section: Tab 3 Experimental D Spacings (In å ) Obtained From Wideanmentioning
confidence: 94%
See 2 more Smart Citations
“…The mesomorphic behavior of poly(MA-co-methacrylate)s is different from that of polymethacrylates 8,13) and poly(MA-alt-1-alkene)s 16,17) . Although all polymers show a decrease of T g with spacer length, only the poly(MAalt-1-alkene)s show an increase in T i with spacer length.…”
Section: Tab 3 Experimental D Spacings (In å ) Obtained From Wideanmentioning
confidence: 94%
“…The synthesis and phase behavior of copolymers containing methoxybiphenyl mesogens will be described. The mesomorphic properties are compared to those of previously described poly(MA-alt-1-alkene)s 16,17) and those of polymethacrylates containing similar mesogens 8,13) . The influence of spacer length and MA content on transition temperatures is studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1,2] These polymers contain methoxybiphenyl mesogens and exhibit smectic mesophases over a temperature range up to 66 8C. SCLCPs with hexyl or longer spacers exhibit a hexatic smectic B and an interdigitated smectic A mesophase.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have already shown that SCLCPs with MA moieties exhibit very interesting physical behavior. [2,11,12] Spincoated films of these polymers on silicon oxide show lamellar ordering upon annealing above the glass transition temperature (T g ). [2,11] In addition, these polymers adhere well on silicon oxide surfaces and exhibit autophobicity.…”
Section: Introductionmentioning
confidence: 99%